2017
DOI: 10.1137/15m1045910
|View full text |Cite
|
Sign up to set email alerts
|

Robust Data Assimilation Using $L_1$ and Huber Norms

Abstract: Abstract. Data assimilation is the process to fuse information from priors, observations of nature, and numerical models, in order to obtain best estimates of the parameters or state of a physical system of interest. Presence of large errors in some observational data, e.g., data collected from a faulty instrument, negatively affect the quality of the overall assimilation results. This work develops a systematic framework for robust data assimilation. The new algorithms continue to produce good analyses in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…A first approach is to set α, and then to estimate the function k → Γ α (k) as defined in Eq. (17). For instance, when N samples from U are available, namely…”
Section: Estimation Of Rrementioning
confidence: 99%
See 1 more Smart Citation
“…A first approach is to set α, and then to estimate the function k → Γ α (k) as defined in Eq. (17). For instance, when N samples from U are available, namely…”
Section: Estimation Of Rrementioning
confidence: 99%
“…Indeed, one definition of the robustness of an estimate is a measure of the sensibility of said estimate to outliers [16]. This leads to the introduction of robust norms in data assimilation [17]. In a Bayesian framework, robustness may refer to the sensitivity to a wrong specification of the priors [18].…”
Section: Introductionmentioning
confidence: 99%
“…Data assimilation using different regularization terms was considered in [30,148], efficient solution techniques for such approaches require ideas from numerical linear algebra.…”
Section: Bayesian Inference and Tikhonov Regularization And Other Asmentioning
confidence: 99%
“…However, minimization involving a L 1 -norm for the regularization (or background) term has also been used and this is found to be particularly useful for tracking sharp fronts and discontinuities (e.g., [ 9 , 10 ]). Rao et al [ 11 ] found L 1 -norm data assimilation to be beneficial when dealing with outlier observations, but had the drawback that solutions lacked smoothness near the mean, this desirable property was retained by using the Huber-norm, a hybrid that utilizes L 1 in the presence of outliers and L 2 close to the mean. An alternative approach to data assimilation, explored by Feyeux et al [ 12 ], utilizes optimal transport theory and within this context the Wasserstein distance (minimizing kinetic energy) replaces the L 2 distance.…”
Section: Introductionmentioning
confidence: 99%